Examining the value of jury critique for architectural design studio courses - Santos, Frederick C. (2020)
Access online through this link: https://journals.upd.edu.ph/index.php/muhon/article/view/7332/6430
Keywords: Architecture studio classes; Critiques (Art education); Architectural design